Analysis of Financial Management Behavior with Financial Technology as a Moderating Variable among Generation Z in Surabaya - Dina Elissa Putri; Dhani Ichsanuddin Nur (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Financial management is an important factor in maintaining financial stability. This has become increasingly relevant for Generation Z, who are entering their productive years and facing various financial challenges. This research was conducted to analyze the factors that influence financial management behavior among Generation Z in Surabaya. Specifically, it examines the influence of financial literacy and lifestyle on financial management behavior, as well as the moderating role of financial technology. A quantitative approach was used, with the population consisting of Generation Z in Surabaya. The study involved 100 respondents selected through purposive sampling. The data used were primary data collected through distributing of questionnaires. The results showed that financial literacy contributes to financial management behavior, as well as lifestyle which also contributes to financial management behavior. In addition, financial technology is proven to contribute to strengthening the influence of financial literacy on financial management behavior. However, financial technology contributes to weakening the influence of lifestyle on financial management behavior.